(untitled) (Marketing Journal, 2026)
Abstract The article examines the issues of improving the management and development mechanisms of food industry enterprises. The study analyzes the current state of enterprise management systems, factors affecting production and financial performance, and mechanisms for shaping development strategies. Special attention is given to the implementation of innovative approaches, digital technologies, and the activation of investment processes to ensure sustainable development of food industry enterprises. The findings are of practical significance for enhancing management processes, increasing competitiveness, and defining long-term development prospects of the sector. Keywords: control mechanism, influencing factors, reforms, food industry, exports, imports, food exports.